2014
DOI: 10.1111/petr.12311
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of a generic of the immunosuppressive agent mycophenolate mofetil in pediatric patients

Abstract: The use of generic immunosuppressive agents is controversial, especially for the treatment of pediatric patients, as information on the bioavailability of generic immunosuppressants in children is particularly scarce. The aim of the study was to compare the bioavailabilities of two products containing mycophenolate mofetil, the innovator and a generic, in children. Pediatric patients with end-stage renal disease on the waiting list for renal transplantation received a single oral dose of mycophenolate mofetil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Moreover, generic immunosuppressants are being administrated to pediatric patients, although information on the bioavailability of these products in children is particularly scarce. Our group has reported that a mycophenolate mofetil generic formulation that is bioequivalent in adults also exhibits a comparable bioavailability with regard to that of the innovator in pediatric patients . However, this does not appear to be the case for certain generic tacrolimus formulations.…”
mentioning
confidence: 97%
“…Moreover, generic immunosuppressants are being administrated to pediatric patients, although information on the bioavailability of these products in children is particularly scarce. Our group has reported that a mycophenolate mofetil generic formulation that is bioequivalent in adults also exhibits a comparable bioavailability with regard to that of the innovator in pediatric patients . However, this does not appear to be the case for certain generic tacrolimus formulations.…”
mentioning
confidence: 97%
“…In the literature, there are some studies on generic MMF; however, most of them concerned adults. González-Ramírez et al [124] compared the innovator product (CellCept ® , Roche, Basel, Switzerland) and the generic (Tevacept ® , Teva Pharmaceuticals, North Wales, PA, USA) in children with end-stage renal disease who were on the waiting list for renal transplantation. Although an important interindividual variability in bioavailability for both MPA formulations was observed, the authors found individual values of AUC within the same range as well as no statistically significant differences in bioavailability parameters between formulations.…”
Section: Additional Information Useful For Mpa Tdmmentioning
confidence: 99%
“…A generic formulation of MMF and mycophenolic acid has been developed and documented to be bioequivalent to the brand name product in healthy adults and kidney transplant recipients 22‐25 . Tevacept has been reported to be bioequivalent to cellcept in a small number of heterogenous group of pediatric transplant recipients 26 …”
Section: General Comments On Generic Substitutionmentioning
confidence: 99%
“…[22][23][24][25] Tevacept has been reported to be bioequivalent to cellcept in a small number of heterogenous group of pediatric transplant recipients. 26 However, in vitro dissolution studies of MMF formulations available worldwide have documented vast differences in the dissolution of various MMF formulations. 27 Patients should be discouraged from ordering generic immunosuppressive drugs from out of the country.…”
Section: Mycophenolic Acidmentioning
confidence: 99%